Evidence of Corporate Zakat Issuance in Sharia Bank in Southeast Asia: Profitability and Liquidity: Bukti Penerbitan Zakat Perusahaan pada Bank Syariah di Asia Tenggara: Profitabilitas dan Likuiditas - Kusuma Wardana, Guntur (Perisai : Islamic Banking and Finance Journal, 2023)
This research aims to examine the effect of ROA, NPM, GPM, BOPO, and FDR, both partially and simultaneously in scientific writing. Islamic banking in Southeast Asia is the subject of research, using the panel data regression analysis method. The type and research approach used is quantitative research with an explanatory approach. Chow test, Hausman test, Lagrange multiplier test, classic assumption test, panel data regression equation test, and hypothesis testing are panel data analysis methods in research. ROA (X1), NPM (X2), GPM (X3), BOPO (X4), and FDR (X5) are the independent variables used in this study. Zakat expenditure of Islamic banking companies is the dependent variable (Y). The results of the study concluded that the ROA and BOPO variables partially had no significant effect on the zakat expenditure of Islamic banking companies in Southeast Asia, while the NPM and GPM variables partially had a significant effect on the zakat expenditure of Islamic banking companies in Southeast Asia. Meanwhile, the ROA, NPM, GPM, and BOPO variables simultaneously have a significant effect on the zakat expenditure of Islamic banking companies in Southeast Asia.